Moroccan diasporic cinema: the 'rooted transnationalism' of the cinéastes de passage. Issue 2 (4th May 2019) - Higbee, Will
ABSTRACT: This article aims to revisit ideas concerning diasporic filmmaking and the transnational originally put forward by the author in the inaugural edition of this journal in 2010. It focuses specifically on the conditions and experiences of diasporic Moroccan filmmakers, considering how their work is produced and circulates on both a global and local level. The article develops the notion of 'rooted transnationalism' to describe the approach of a specific group of diasporic filmmakers: the cinéastes de passage. The cinéastes de passage are Moroccan filmmakers whose movement between the West and Maghreb is dictated by the political, artistic and economic conditions of each new project and who maintain a presence both within and between the cinematographic cultures and industries in Europe and Morocco. The article argues that these filmmakers have played a key role in the success, diversity and transnational visibility of Moroccan cinema over the past 25 years.